The World Bank : a critical analysis - Payer, Cheryl, 1940- 4 0 16; 5 (New York : Monthly Review Press, 1982)
A careful analysis of the Bank's own policy papers and reports, which outlines its philosophy of development and the concrete effects of its projects. -- Publisher description.
1. The Institution and its power --- 2. Malignant growth: a preliminary explanation --- 3. Project lending: some general considerations --- 4. Infrastructure: the traditional sectors --- 5. Industry --- 6. Mining --- 7. Oil and gas --- 8. Agriculture and rural development --- 9. Water resources --- 10. Forestry and tree farming --- 11. Urban shelter projects --- 12. Inside the Bank --- Conclusion: is there a better way?
Includes bibliographical references and index.
Keywords: 2 -- 0; World Bank. -- 6; World Bank; 20; 2